Vitamin C Level in Pregnant Women with Premature Rupture of the Membrane (PROM) and in Women with Normal Pregnancy - Sarah Rizka (Indonesian Socety of Obstetrics and Gynecology, 2011)
Objective: To compare vitamin C level in term pregnant women with PROM and in women with normal pregnancy. Method: This is a cross sectional study, research from July 2010 until June 2011. Inclusion criteria are full term pregnant women with and without PROM. After the diagnosis is confirmed as PROM, mothers blood was taken from mediana cubiti venous to check the vitamin C level and leucocytes in mothers serum. Pregnancy with complication is the exclusion criteria. Result: There were 52 subjects that fulfilled the acceptance and rejection criteria after divided into 2 groups, the 1st group was with PROM and the 2nd groups were normal. Based on the laboratory examinations, the mean of vitamin C levels in PROM groups is 0.731 ± 0.182 μg/dl and the normal groups is 0.722 ± 0.169 μg/dl, there is no significant difference (p=0.852). Leucocyte examination was done to know whether there was infection or not. The mean value from the PROM groups is 14330.77 ± 6552.90 μg/dl. And from the normal groups is 12973.08 ± 4160.24 μg/dl, there is significant difference (p=0.377). Conclusion: There is no significant difference of Vitamin C level between maternal plasma with PROM and the one without PROM. [Indones J Obstet Gynecol 2011; 35-4:173-5] Keywords: PROM, normal pregnancy, vitamin C